A FUZZY RECOGNITION MODEL FOR ARABIC HANDWRITTEN ALPHABET (Journal of Engineering, 2008)
A fuzzy recognition model for some handwritten Arabic alphabet is designed. This fuzzy model could be envisaged as an algorithm which is structured over two concepts. First; the handwritten character variation is modeled by the fuzziness of the feature vector's elements. Second; the notion of entropy is fuzzily modified to extract the amount of information in the elements within the feature vector so as to speed up the recognition process. Consequently, a fuzzy recognition graph of the optimum paths decision tree is designed for the handwritten Arabic alphabet character's recognition.